2015
DOI: 10.1016/j.ijcard.2015.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic respiratory parameters in heart failure patients with and without exercise oscillatory ventilation — A systematic review and descriptive meta-analysis

Abstract: The purpose of this review was to describe the occurrence of prognostic variables as derived from cardiopulmonary exercise testing (CPET) in patients with heart failure (HF), presenting exercise oscillatory ventilation (EOV) compared to patients without EOV. The effect of EOV on peak oxygen consumption (VO2), minute ventilation/carbon dioxide production (VE/VCO2) slope, oxygen uptake efficiency slope (OUES), rest and peak pulmonary end-tidal carbon dioxide pressure (PETCO2) was meta-analysed. A systematic sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 58 publications
1
27
2
Order By: Relevance
“…One study has showed that the presence of the combination EOV and VE/VCO 2 > 34 is particularly more alarming because of the risk for adverse cardiac events [ 18 ] . Otherwise, our results do not agree with the literature when it comes to the worst response of CET variables on EOV population, described as lower peak VO 2 , higher VE/VCO 2 slope, and lower rest and peak P ET CO 2 , when compared to non-EOV population [ 17 ] . Hypotheses for these findings are the heterogeneity of exercise protocols in the literature and the absence of a gold standard to verify the presence of EOV in patients with profile and clinical status similar to our subjects.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…One study has showed that the presence of the combination EOV and VE/VCO 2 > 34 is particularly more alarming because of the risk for adverse cardiac events [ 18 ] . Otherwise, our results do not agree with the literature when it comes to the worst response of CET variables on EOV population, described as lower peak VO 2 , higher VE/VCO 2 slope, and lower rest and peak P ET CO 2 , when compared to non-EOV population [ 17 ] . Hypotheses for these findings are the heterogeneity of exercise protocols in the literature and the absence of a gold standard to verify the presence of EOV in patients with profile and clinical status similar to our subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Other CET variables showed similarities between our study and the literature, specifically when it comes to the coexisting presence of EOV and other bad prognostic variables, such as VE/VCO 2 > 34 and peak VO 2 < 14 ml/kg/min [ 17 ] . One study has showed that the presence of the combination EOV and VE/VCO 2 > 34 is particularly more alarming because of the risk for adverse cardiac events [ 18 ] .…”
Section: Discussionsupporting
confidence: 77%
“…The Harvard step test is an accepted tool to evaluate tolerability to physical exercise [47]. Higher values of this measure related to a lower incidence of cardiopulmonary disease and better predisposition or physical activity [48,49]. Here, the Harvard step test showed an improvement in oxygen consumption and energy expenditure after the intervention with inhaled NaHCO 3 ( Table 2).…”
Section: Discussionmentioning
confidence: 84%
“…2 A meta-analysis of studies reporting hazard ratios (HRs) for cardiovascular events demonstrated that HF patients with EOV have a 4-fold higher risk for adverse events than HF patients without EOV. 3 EOV is now considered a marker of disease severity and worse prognosis in HF. 3,4 Despite the clear association between EOV and outcomes in HF, there are limited data regarding the mechanistic basis for EOV.…”
mentioning
confidence: 99%
“…3 EOV is now considered a marker of disease severity and worse prognosis in HF. 3,4 Despite the clear association between EOV and outcomes in HF, there are limited data regarding the mechanistic basis for EOV. 5 Moreover, only a few studies have evaluated the association between EOV severity and prognosis of HF patients with EOV.…”
mentioning
confidence: 99%